Existem línguas de ritmo silábico? - Cagliari, Luiz Carlos [UNESP] (My University, 2013)
The language typology of speech rhythm has been investigated by many researchers in different languages. However, they have not reached a unanimous conclusion. Part of the misunderstanding is due to the methodology they used. In addition, there is some theoretical confusion on the definition of a syllable timed language. This paper refers to the last question, but without discussing others people works and theories. Instead, it points out some essential questions that have not been taken into consideration in the discussion.

A tipologia do ritmo das línguas tem sido investigada por muitos pesquisadores de várias línguas, porém, sem que eles tenham chegado a conclusões unânimes. Parte das divergências se deve às metodologias usadas. Há também muita confusão teórica a respeito do que seria uma língua de ritmo silábico. O presente trabalho contempla esse último aspecto, sem introduzir discussões com trabalhos e teorias desenvolvidas, apenas chamando a atenção para alguns pontos importantes, nem sempre levados em consideração nessa discussão.
Do syllable-timed languages exist?
Keywords: Speech rhythm; typology; syllable-timed rhythm; Ritmo da fala; Tipologia; Língua de ritmo silábico